2015
DOI: 10.1590/1982-7849rac20151488
|View full text |Cite
|
Sign up to set email alerts
|

Orgulho de Ser Brasileiro Impacta o Nível de Felicidade?

Abstract: Resumo Na última década tem-se verificado um expressivo crescimento do número de trabalhos dedicados à identificação de determinantes do bem-estar subjetivo dos indivíduos. Contudo, um importante preditor do bem-estar tem sido pouco estudado, o orgulho nacional, em especial nos países latino-americanos. A partir de uma abordagem comparada entre o Brasil e demais países latino-americanos, este artigo verifica a existência de associações entre o sentimento de orgulho nacional e o nível de bem-estar dos indivíduo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In the case of Brazil, studies have endorsed many of the findings shown by the international evidence (CORBI;MENEZES-FILHO, 2006;ISLAM et al, 2009;RIBEIRO, 2015;RIBEIRO;MARINHO, 2017;GOLGHER, 2014aGOLGHER, , 2014bGOLGHER, , 2014c. Other studies compared Brazil with other countries (CAVALCANTI et al, 2009;ONUSIC;MENDES-DA-SILVA, 2015) or included Brazil in a broader context (GRAHAM;PETTINATO, 2001;GRAHAM et al, 2011). Thus, the topic discussed in this paper has already been addressed by different methodologies and approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Brazil, studies have endorsed many of the findings shown by the international evidence (CORBI;MENEZES-FILHO, 2006;ISLAM et al, 2009;RIBEIRO, 2015;RIBEIRO;MARINHO, 2017;GOLGHER, 2014aGOLGHER, , 2014bGOLGHER, , 2014c. Other studies compared Brazil with other countries (CAVALCANTI et al, 2009;ONUSIC;MENDES-DA-SILVA, 2015) or included Brazil in a broader context (GRAHAM;PETTINATO, 2001;GRAHAM et al, 2011). Thus, the topic discussed in this paper has already been addressed by different methodologies and approaches.…”
Section: Introductionmentioning
confidence: 99%